Steep slope DEM model construction based on the unmanned aerial vehicle (UAV) images - Xi, Wenfei; Li, Dongsheng (Penerbit Universiti Kebangsaan Malaysia, 2017)
The DEM construction of high and steep slope has great importance to slope disaster monitoring. The conventional method used to construct high and steep slope DEM model requires larger field surveying workload. First of all, the high and steep slope image was obtained through unmanned aerial vehicle (UAV) platform; Then the SIFT algorithm is used to extract the feature points which are going to be matched accurately by using RANSAC algorithm. Finally, stereo pair splicing method is used to generate orthogonal images and construct DEM model. After comparing the DEM model with actual slope measurement result collected by total station finding, it is shown that elevation error between the DEM model constructed by unmanned aerial vehicle (UAV) and actual measurement is minimal and its efficiency is proven.